PENGARUH TINGKAT ABSENSI DAN KEDISIPLINAN KARYAWAN TERHADAP PRODUKTIVITAS KERJA PADA PT. XYZ - Ucah Nurcahyati; Hendra Permadi (Jurnal Cakrawala Ilmiah, 2023)
To achieve high work productivity, it is determined by the human behavior itself carrying out the work. Given the magnitude of the role and position of human resources as workers in a company. The problems in this study are related to the effect of absence on work productivity, the effect of discipline on work productivity, and the effect of absenteeism and discipline on work productivity at PT. XYZ. Associative research is research that aims to determine the relationship of two or more variables. This research used 60 respondents. Based on the results of the study findings independent variables, were absentee levels (X1) and Discipline (X2) have a significant effect on the work productivity variable at PT. XYZ either partially or simultaneously. While the results of the determination test show that 63.9% of the Absenteeism and Discipline Level variables can affect Work Productivity at PT. XYZ, while the remaining 36.1% is influenced by other variables not examined by the authors. PT. XYZ implements a stricter and more consistent level of attendance and discipline for all employees and improves supervision of employees who are working.